A method of lower and upper solutions for control problems and application to a model of bone marrow transplantation - Parajdi, Lorand Gabriel; Precup, Radu; Haplea, Ioan Ştefan (Zielona Góra: Uniwersytet Zielonogórski)
A lower and upper solution method is introduced for control problems related to abstract operator equations. The method is illustrated on a control problem for the Lotka-Volterra model with seasonal harvesting and applied to a control problem of cell evolution after bone marrow transplantation.
Keywords: control problem; lower and upper solutions; fixed point; approximation algorithm; numerical solutions; medical application